Intrauterine insemination: a UK survey on the adherence to NICE clinical guidelines by fertility clinics. Issue 5 (15th May 2015) - Kim, Dongah; Child, Tim; Farquhar, Cynthia
Abstract : Objective: To evaluate the awareness and response of fertility clinics in the UK to the National Institute for Health and Care Excellence (NICE) guideline recommendation that intrauterine insemination (IUI) should not be offered routinely, in order to report on current practice in the UK. Design: Online questionnaire survey of fertility clinics in the UK regarding their current clinical practice of IUI, formal discussion of the guideline recommendations, and any alterations made since the recommendations. Setting: 66 UK fertility clinics licensed to provide IUI. Participants: 46 fertility clinics, including 6 clinic groups which represent 70% of all clinics and clinic groups licensed to provide IUI in April 2014 when the survey email was sent. Results: Of the 46 clinics that responded, 96% (44/46) of clinics continue to offer IUI. 98% (43/44) of those offering IUI also use ovarian stimulation. The most commonly used medications for ovarian stimulation are gonadotrophins (95%), followed by clomiphene citrate (49%) and letrozole (19%). 78% (36/46) of clinics had formally discussed NICE guideline recommendations. 17 clinics (37%) had made some changes to their practices; as a result, four clinics reported a reduction in the number of IUI cycles, six clinics had restricted the indications for IUI, and five clinics had begun informing patients of the guideline recommendations, while two did not specify. Conclusions: The majority of clinics were aware of the guideline recommendations. However, only a small proportion of clinics had made significant changes to their practice by reducing the number of IUI cycles or restricting the clinical indications for IUI. The availability of further evidence will assist NICE and clinicians in making recommendations on the use of IUI. There is a need to further explore the reasons for the lack of adherence to the recommendations.